Upaya Meningkatkan Kemampuan Menghitung melalui Media Konkret Koin Warna (Kancing) pada Mata Pelajaran Matematika Madrasah Ibtidaiyah - Mulyawati, Mulyawati; Tantowie, Tanto Aljauharie; Fuadi, Diki Najib (Bestari, 2019)
This research is based on the low learning outcomes of students in the ability to calculate class II MIS Pasirlingga on learning Mathematics subject of Operation Mixed Count. One attempt to improve students' numeracy skills, researchers used Concrete Coins Color Media. The method used is Classroom Action Research Method (PTK) model Kurt Lewin. Data collection techniques used are observation, interview techniques, test and description analysis techniques. Based on research data and data analysis results, obtained conclusions, namely 1) the ability of teachers in designing the implementation planning of learning mathematics reached 90.17; 2) teachers' skills in the implementation of Mathematics learning reached 90.78; and 3) student learning outcomes reach an average value of 80. This proves that the concrete media of color coins affect the improvement of students 'counting ability and students' counting ability will influence student learning outcomes.